Barn i förskolan med annat modersmål än svenska : Flerspråkighetens betydelse för barn - Nyström, Helen; Wennberg, Johanna (2013)
In this study, we interviewed four teachers and a principal on multilingualism importance for children. The interviews took place in two different municipalities in northern Sweden, in preschool and school. We chose to use qualitative interviews to answer our issues. In this study, we found that all respondents believe that multilingualism is important for children. However, respondents differed concerning native support, but very agree that there are some disadvantages to the child's development. Validerat; 20130303 (global_studentproject_submitter)